Midwifery and mental health : narratives of New Zealand midwives : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, New Zealand - Hielkema, Karen Ann Marie (Massey University, 2014)
New Zealand has a midwife-led maternity system, and over 75% of women engage an independent midwife for maternity care. It is estimated that one in four mothers will experience symptoms of psychological disorder in the ante-and post-natal period. This research questions the meaning of a pathological maternal body and symptoms of anxiety through the experience of midwives. Developed through consultation with midwives and feminist standpoint epistemology, this research aimed to understand how midwives are narratively positioned in their practice and how midwifery ideology could inform psychological practice in maternal mental health. As a feminist project, the research accounted for what was salient to the midwives and how working with clients with mental health issues impacted on them personally and professionally. To bring voice to the narratives produced through twelve interviews, a feminist standpoint epistemology was engaged to locate midwives in their own ideological framework, and the political and institutional power relations in which they are embedded. Researcher reflexivity, the context of tensions between midwifery and biomedical discourse, and the contradictory meaning of the maternal body were brought to the analysis. A structured approach to narrative analysis brought meaning to how midwives’ identities and experiences intersect at ideological, personal, interpersonal and professional levels. The structural analysis allowed for an understanding of the complexities faced by New Zealand’s midwives in their practice. It enabled an understanding of the technologies of gendered power relationships that produce the maternal body through the medical gaze, and the effects for midwives as they oscillate between biomedical and midwifery ideological narratives of maternity and maternal mental health. It also provides an understanding of the effects of narratives of risk where biomedical narratives produce the maternal body as deficit physiology and psychology, particularly reducing women’s distress to a symptom of disorder and excludes the sociocultural context of women’s experience.
Keywords: 420403 Psychosocial aspects of childbirth and perinatal mental health